Pertumbuhan dan Hasil Kedelai (Glycine Max (L.) Merr.) Pada Pemberian Pupuk Kandang Kambing Dan Bio-Growth - Jakoni Jakoni; Wisnu Giri Madani; Tiara Septirosya (Savana Cendana, 2022)
Soybean is one of the third most essential crops after rice and maize, whose production still needs to be increased. One of the efforts to utilize less fertile land is using organic fertilizers in goat manure and Bio-Growth. This study aimed to obtain the best dose of goat manure and Bio-Growth for soybean growth and yield. This research has been carried out at the experimental garden of the Kubang Research and Assessment of Agricultural Technology (BPTP) Balitbangtan Riau from August to November 2021. The method is practical with a factorial Randomized Block Design (RBD) consisting of 2 factorials with 3 replications. The first factor is goat manure (K0: 0 tons/ha, K1: 10 tons/ha, and K2: 20 tons/ha); the second factor is Bio-Growth (B0: 0 ml/4 l water, B1: 72.5 ml/4 l water, B2: 145 ml/4 l water, and B3: 217.5 ml/4 l water). The height of the plant, the number of its leaves, the diameter of its stem, the number of its branches, the number of pods produced by each plant, the weight of pods produced by each plant, the total weight of pods, and the weight of one hundred seeds were all measured. The application of goat manure and Bio-Growth influenced the height of the plant, the number of leaves, the number of pods produced by each plant, the weight of each pod, the total weight of the pods, and the weight of one hundred seeds. It was determined that the interaction between the two treatments did not impact all experimental parameters. This study concludes that the best application of goat manure is 10 tons/ha, while the most efficient Bio-Growth dose of 72.5 ml/4 l of water can increase the growth and yield of organic soybeans.